Há 100 anos, a descoberta do Treponema pallidum A hundred years ago, the discovery of Treponema pallidum - Elemir Macedo de Souza (Sociedade Brasileira de Dermatologia, 2005)
A descoberta do Treponema pallidum por Schaudinn & Hoffmann em 3 de março de 1905 foi influenciada pela comunicação de Siegel, sobre a descoberta do agente etiológico da sífilis. Encarada com ceticismo, a comunicação acarretou novas investigações, conduzidas pelo zoologista Schaudinn e pelo dermatologista Hoffmann -primeiros observadores do agente da sífilis, denominado Spirochaeta pallida. A descoberta foi o passo inicial para o desenvolvimento dos procedimentos diagnósticos e terapêuticos nos anos subseqüentes. The discovery of Treponema pallidum by Schaudinn & Hoffmann, on March 3rd 1905, was influenced by Siegels' communication on the finding of the etiological agent of syphilis. John Siegel, working at the Institut of Zoology, University of Berlin, claimed to have found a flagellate protozoon in syphilitic lesions. Because of the skepticism it was received with, this communcation yielded further investigation, conducted by zoologist Schaudinn and dermatologist Hoffmann. They were the first investigators to find the etiological agent of syphilis, described under the name of Spirochaeta pallida. The discovery of Treponema pallidum on March 3rd 1905 was the first step towards the development of diagnostic and therapeutic procedures in subsequent years.